(untitled) («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
The article talks about the unique feature of morpheme dictionaries, a type of dictionary that differs from other dictionaries by incorporating morpho-syntactic, morpho- phonemic, morpho-orphepic and morpho-orthographic features of words. will go. Also, studies on lexicographic features of morpheme dictionaries are analyzed.